Pengaruh Model Pembelajaran Mandiri Terhadap Hasil Belajar Agama Kristen Dan Budi Pekerti Peserta Didik Kelas XI SMA Negeri 1 Siborongborong Tahun Ajaran 2022/2023 - Asni Nazara; Hasudungan Simatupang; Robinhot Sihombing (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This research aims to determine whether there is a positive and significant influence between the Independent Learning Model on the Christian Religion and Moral Learning Outcomes of Class Characteristics of Class XI Students at SMA Negeri 1 Siborongborong for the 2022/2023 Academic Year. This research uses a descriptive and inferential quantitative approach, with a population of all Class XI students at SMA Negeri 1 Siborongborong totaling 354 people with a sample of 35 people. Data was collected using a closed questionnaire of 20 items compiled by the author based on variable indicators according to expert theory and a test of 20 items both through pre-test and post-test. Testing of questionnaires and questions was carried out on 30 students at SMA PGRI 20 Siborongborong, and validity and reliability were tested. The results of data analysis show that there is a positive and significant influence of the Independent Learning Model on the Christian Religion and Character Learning Outcomes of Class (r2) = 16.73% through the post test and the significant influence test obtained tcount>ttable of 2.834>2.042 through the pre test and tcount>ttable of 4.778>2.042. The Fcount price is compared with the Ftable price with dk in the numerator = 1 and dk in the denominator (n-1 = 35-1=34) with an error rate of 5%, so the Ftable price = 4.17. In this case, the provisions apply if Fcount < Ftable means the variance is homogeneous and vice versa if Fcount > Ftable means the variance is not homogeneous. Based on the data obtained, it can be concluded that the research hypothesis is that there is a positive influence between the Independent Learning Model on the Christian Religion and Character Learning Outcomes of Class XI Students at SMA Negeri 1 Siborongborong for the 2022/2023 Academic Year. Thus, H0 is rejected and Ha is accepted